PENGARUH MANAJEMEN KONFLIK TERHADAP KINERJA PEGAWAI PADA LPP TVRI STASIUN KALIMANTAN SELATAN - Muhammad Agus Humaidi; Musliadi Musliadi (LP2M IAI Muhammadiyah Sinjai, 2022)
This study aims to determine conflict management and employee performance at LPP TVRI South Kalimantan Station, in addition to knowing the effect of conflict management on employee performance at LPP TVRI South Kalimantan Station. The method used is a quantitative research approach and research instruments with questionnaires analyzed with Chi Square Goodness Of Fit and Simple Linear Regression. The results showed that employee conflict management at LPP TVRI South Kalimantan Station was categorized as quite good. Meanwhile, the performance of employees at LPP TVRI South Kalimantan Station is in the good category. In addition, there is a significant influence between conflict management on employee performance at LPP TVRI South Kalimantan Station